1990
DOI: 10.1037/0735-7028.21.4.291
|View full text |Cite
|
Sign up to set email alerts
|

Mental health values and preference for mental health resources of Japanese-American and Caucasian-American students.

Abstract: The authors investigated Asian-American underuse of mental health resources as a function of attitudes about the nature of mental health (mental health values) and resource preference for assistance with serious personal problems, with 91 Caucasian-American and 90 Japanese-American undergraduates. Mental Health Values Questionnaire (MHVQ) results revealed that Japanese Americans more strongly related several MHVQ scales to mental health (good interpersonal relations, trustworthiness, and absence of negative pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 29 publications
2
26
1
Order By: Relevance
“…This preference for informal helping agents also extends to Chinese students (Cheung, 1984). In addition, Asian families in the United States have been found to underutilize mental health services and to overutilize informal sources of support, in comparison with other ethnic groups (Suan & Tyler, 1990). There is limited published research on adolescent help-seeking behavior in Asia.…”
Section: A Study Of Help-seeking Behavior Among Secondary School Studmentioning
confidence: 96%
“…This preference for informal helping agents also extends to Chinese students (Cheung, 1984). In addition, Asian families in the United States have been found to underutilize mental health services and to overutilize informal sources of support, in comparison with other ethnic groups (Suan & Tyler, 1990). There is limited published research on adolescent help-seeking behavior in Asia.…”
Section: A Study Of Help-seeking Behavior Among Secondary School Studmentioning
confidence: 96%
“…Whether or not mental health treatment is sought depends on individuals' perception of its helpfulness as well as one's conception of the nature of emotional problems. Among many Asians, emotional distress is seen as the result of malingering bad thoughts, a lack of will power, and personality weakness~Kitano, 1969; Narikiyo & Kameoka, 1992;Suan & Tyler, 1990;Sue & Morishima, 1982! ; thus self control and solving one's own problems are culturally valued over seeking help~Boey, 1999;Loo et al, 1989;Zhang, Snowden & Sue, 1998!.…”
Section: Background Literaturementioning
confidence: 99%
“…Since causal attribution (Baumann, 2003;Kirmayer et al, 1994) and sources of help (Kirmayer, 2004: Kleinman, 1980 are better understood in a sociocultural context, it is relevant to discuss their relationship based on Asian studies here. Past research has shown that Asians, even though suffering from a wide range of emotional distress, are less likely than Westerners (predominantly white North Americans) to utilise mental health services (Huang & Spurgeon, 2006;Leong & Lau, 2001;Suan & Tyler, 1990). This phenomenon may be due to stigmatisation of mental disorders, somatisation, shame and 'face saving', linguistic barriers, inadequate number of culturally competent mental health professionals, inaccessibility of services, value conflicts with service providers, not being familiar with the Western mode of mental health services, and negative attitudes towards seeking psychological help (Chen, Sullivan, Lu, & Shibusawa, 2003;Leong & Lau, 2001;Spencer & Chen, 2004;Sue & Sue, 2008;Yeh, 2002).…”
Section: Causal Attribution Of Emotional Symptoms and Preferred Sourcmentioning
confidence: 99%